A bootstrap analysis to investigate the economic efficiency of the logistics industry in Italy*. Issue 1 (2nd January 2018) - Ferrari, Claudio; Migliardi, Andrea; Tei, Alessio
ABSTRACT: As argued by literature and consultancy reports, logistics enhances both productivity and competitiveness of several manufacturing supply chains. The analysis of the efficiency trends of logistics providers may shed light on some relevant aspects that can impact on the competitiveness of national industrial systems. Thus, the paper focuses on the Italian logistics supply, shedding lights on the distribution of the efficiency level within the logistics sector and its causes. The analysis is based on a two-stage methodology aimed at estimating the Italian logistics firms' efficiency and defining some characteristics impacting the efficiency level. At first, we implement a Data Envelopment Analysis model based on balance sheet data, for the period 2006–2012, then an econometric regression is performed in order to identify the effects of main companies' characteristics on firms' efficiency. According to our results, size and geographical location are two of the most impacting variables explaining the efficiency score of the Italian logistics providers.